Seroepidemiological monitoring in sentinel animals and vectors as part of arbovirus surveillance in the state of Mato Grosso do Sul, Brazil - Paulo Mira Batista; Renato Andreotti; Jannifer Oliveira Chiang; Milene Silveira Ferreira; Pedro Fernando da Costa Vasconcelos (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: From February-September 2010, seroepidemiological surveys were conducted on non-human primates and transmitter vector capture was used to investigate the possible circulation of arboviruses in the municipalities of Bonito, Campo Grande, and Jardim, State of Mato Grosso do Sul, Brazil. METHODS: A total of 65 primates from the wild and captivity were used, and potential vectors were captured using Castro and dip nets. Serum samples were tested at the Instituto Evandro Chagas, State of Pará, using the hemagglutination inhibition test to detect total antibodies against 19 different arboviruses. Virus isolation was attempted from serum samples and arthropod suspensions using newborn mice and the C6/36 cell line clone. In addition, identification of the vector species was conducted. RESULTS: From the 19 serum samples from Campo Grande, 1 sample had a 1:20 titer for Flavivirus. From the 35 samples collected in Bonito, 17 samples had antibodies to arboviruses, 4 (11.4%) were positive for Alphavirus, and 5 (14.2%) were positive for Flavivirus. Monotypic reactions were observed for the Mayaro (n = 10) and Oropouche (n = 5) viruses, and 6 (17.1%) samples had titers for >1 virus. We captured 120 Culicidae individuals that were potential arbovirus transmitters in Jardim; however, all the samples were negative for the viruses. CONCLUSIONS: Mato Grosso do Sul has a variety of vertebrate hosts and transmission vectors, thereby providing ideal conditions for the emergence or reemergence of arboviruses, including some pathogenic to human beings.